Cultural Heritage of Russia in the Patriotic Education on the Eve and During the Great Patriotic War - Nina Konstantinovna Gurkina; Aleksey Petrovich Isaev (Управленческое консультирование)
The article considers experience of use in the cultural and ideological work of the party and the state of historical knowledge and cultural heritage as a tool of the Patriotic education and «spiritual mobilization» of the nation on the eve and in the first years of the great Patriotic war.